Eksplorasi Peran Kompensasi dan Kinerja Karyawan pada Retail Berbasis Komunitas - Lussia Mariesti Andriany; Sofiana Cahyani (Institut Teknologi dan Sains Mandala, 2025)
The main argument in this paper is that the relationship between compensation and performance should be recognized as reciprocal, in which, commonly, compensation received by employees will impact their performance. However, there is another logic that emerges whereby employees’ performance becomes an important basis for an organization to settle their compensation. Thus, this current research aims to re-explore the relationship between compensation and performance. Conducting qualitative approach, specifically grounded theory method, this research takes community-based retail as its research object. Data was gathered through semi-formal interview procedure to six organization members, namely owner and employees. Those two groups of informants were interviewed to validate the data through source triangulation. Data was analyzed using Miles and Hubermann procedures and displayed utilizing Gioia template. Based on the analysis, it is confirmed that compensation and performance relationship is reciprocal. The compensation itself consists of financial and non-financial, whereas employee can be measured using three parameters which are employees’ ability, responsibility, and discipline.